REVEALING HIDDEN POLITICAL AGENDA IN THE PRESENTATION OF MARTIN AS A ZOOPHILE IN EDWARD ALBEE’STHE GOAT, OR WHO IS SYLVIA? - FATIMAH, - (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: deviant sexual orientation, zoophile, queer politics, the goat, or who isSylvia? Social phenomenon shows a significant and rapid movement toward the existence of deviant sexual orientation, like zoophilic, a sexual desire to the animals. In assessing the whole life of a zoophile, people are preferable to use some prejudices which attach behind their sexual desire. A drama entitled The Goat, or Who is Sylvia? is interested in portraying about the life of a zoophile in the presentation of the main character named Martin. Yet, this drama describes his image as different from the preconceived notion of society. Hence, it emerges a question that this drama may have political interest toward the existence of a zoophile in the society. Therefore, this research is conducted to verify about this premise.This research uses queer theory, specifically queer politics to investigate the political purposes behind the normalization of a queerness to reject intolerance and discrimination in the society. Besides, this research also applies a qualitative approach through document analysis to examine the data taken from the drama.Some forms of normalization are used to depict the life of a zoophile. First, this drama presents Martin to have 4 (four) positive and 2 (two) major negative traits. Besides, his normalization also covers 3 (three) social roles fulfillment as a part of family and peers group. Furthermore, other presentation shows that he has 2 (two) higher achievement as a smart and successful person. Those findings finally can detect the intention of this drama to portray the real life of a zoophile. It happens because queer politics views that zoophile also undergoes the same life as other normal people, thus a zoophile does not deserve to be treated bad among the society.Based on the study findings, this research concludes that the presentations of Martin have a political purpose to gain societal acceptance for alleviating intolerance and discrimination toward the existence of a zoophile. Furthermore,  the next research can be suggested to explore this drama in term of his psychological perspective while having inner conflict to come out as a zoophile or his surrounding responses to reject his zoophile identity using socio-psychological approach.